PENYULUHAN POLA TANAM EMPON-EMPON DAN PEMBUATAN KOMPOS DI BALAI DESA GROWONG KECAMATAN TEMPURAN KABUPATEN MAGELANG - Rita Kuntarti; Mardjitulastri; Agustin Nur Handayanti (PPM Sdirjianbang Akademi Militer, 2022)
One indicator development said succeed if come true source power quality human. Problems that arise on a number of regions in Indonesia, still many found area included _ category left behind in well- being , left behind in development knowledge knowledge and technology as well as left behind in empower source power natural nor source power the human . This thing will impact on level well-being as well as progress something area . Source power man said quality when have knowledge , skills and ability . Growong is wrong one area or the area in the district Combat districts Magelang which has contour mountains with eye livelihood farmer and partially laborer farmer . Besides that , there is a number of plantation plant hard like sengon , teak , and pine . Source power people in the village Growong not yet fully said quality , thing this showed with still a lot land left blank _ abandoned as well as a lot waste unfinished rice _ utilized with good . See a number of problem that , Lecturer Akmil choose village Growong as area Devotion to Public as form implementation of the Tri Dharma College high . Service Team to Public this aim for increase quality source power man and increase well-being house ladder with holding hands a number of agency government related , such as District Plantation Office Magelang , and government local as owner region . Efforts made _ team Devotion to Public use method counseling and demonstration next practice by straight away . Method counseling conducted as supplies theory and practice direct through activity utilization plant empon-empon / herbal rhizome ( ginger , lemongrass , turmeric ) through system intercropping and _ making fertilizer compost made from base husk rice. From result Devotion to Public by direct could seen from big enthusiastic inhabitant in follow counseling nor practice . Realization a number of demolot ( pilot model plot plant empon-empon ) and realization Skills inhabitant utilise waste paddy Becomes useful stuff _ as well as produce through making fertilizer compost . Hope from team Devotion to Public activity this will Keep going sustainable with professionally through _ a number of group that has there is like Group farmer and Bumdes ( Badan Usaha Milik Desa ) which on moment implementation devotion the building new built .